High absolute neutrophil count with type 2 diabetes is associated with adverse outcome in patients with coronary artery disease: A large-scale cohort study - He, Jining; Lin, Zhangyu; Song, Chenxi; Zhang, Rui; Wang, Haoyu; Yuan, Sheng; Bian, Xiaohui; Dong, Qiuting; Dou, Kefei (Frontiers in Endocrinology, 2023)
Background: Inflammatory processes crucially modulate the development, progression, and outcomes of coronary artery disease (CAD). Since hyperglycemia could alter inflammatory responses, this study aimed to investigate the effect of ANC, a novel rapidly available inflammatory biomarker, on prognosis of patients undergoing PCI with or without type 2 diabetes (T2D). Methods: A total of 7,826 patients with CAD hospitalized for PCI at Fuwai hospital were consecutively recruited. According to median ANC value, patients were stratified as high ANC (ANC-H) and low ANC (ANC-L) and were further classified into four groups by T2D. The primary endpoint was major adverse cardiovascular and cerebrovascular events (MACCEs), including all-cause mortality, myocardial infarction, stroke and target vessel revascularization. Results: During a median follow-up of 2.4 years, 509 (6.5%) MACCEs were documented. Diabetic patients with increased ANC were at significantly higher risk of MACCEs (aHR, 1.55; 95%CI, 1.21-1.99; P=0.001) compared to those in the ANC-L/non-T2D group (P for interaction between T2D and ANC categories=0.044). Meanwhile, multivariable regression analysis demonstrated the highest MACCE risk in diabetic patients with higher level of ANC than others (P for trend <0.001). Conclusions: This study suggests stratification of patients with elevated ANC and T2D could provide prognostic information for CAD patients undergoing PCI.